VIRGINIA WOOLF THROUGH IMAGES AND WORDS GRAPHIC BIOGRAPHIES OF VIRGINIA WOOLF - Elisabetta VARALDA (Linguarum Universe, 2025)
This paper arises from a feeling that scholars have mainly focused their attention on the influence of Woolf’s life on contemporary narratives written in prose, while there is a lack of research on graphic biographies, which rewrite the lives of canonical historical authors. By examining five graphic biographies [Alessandro Bacchetta’s Una stanza tutta per tre (2013), Lucrèce’s Virginia (2017), Lady Desidia’s El jardίn secreto de Virginia Woolf (2020), Liuba Gabriele’s Virginia Woolf (2021), and Susanne Kuhlendahl’s Virginia Woolf (2021)], I aim to illuminate how graphic biographies, and the compelling practice offered by the visual-verbal form, have the merit of making a significant contribution to continuing Woolf’s iconicity and literary tradition in the twenty-first century.Moreover, since they are written in Italian, Spanish, and German, my aim is to demonstrate how Woolf’s iconicity has transcended the boundaries of the Anglo-American world and how these biographies provide a unique opportunity to broaden the already existing interest in Woolf. The artists, who are the focus of this paper, not only recreate a life by borrowing facts, details and events from Woolf’s real life, but they are also intertextually related to her fictional world since their biographies include fragments of her works within themselves, highlighting the palimpsestic nature of life writing through Woolf’s life story. Thus, this paper is especially indebted to the theoretical positions developed by Gerard Génette, who invites us to study the relationships that link a text to other texts, and by Frassen and Hoenselaars, who suggest considering earlier authors’ lives as texts, which contemporary authors can appropriate.